Discoidin Domain Receptor-Driven Gene Signatures as Markers of Patient Response to Anti–PD-L1 Immune Checkpoint Therapy. (3rd August 2022) - You, Sungyong; Kim, Minhyung; Hoi, Xen Ping; Lee, Yu Cheng; Wang, Li; Spetzler, David; Abraham, Jim; Magee, Dan; Jain, Prerna; Galsky, Matthew D; Chan, Keith Syson; Theodorescu, Dan
Abstract: Background: Anti–programmed cell death 1 (anti–PD-1) and PD ligand 1 (PD-L1) immune checkpoint therapies (ICTs) provided durable responses only in a subset of cancer patients. Thus, biomarkers are needed to predict nonresponders and offer them alternative treatments. We recently implicated discoidin domain receptor tyrosine kinase 2 (DDR2 ) as a contributor to anti–PD-1 resistance in animal models; therefore, we sought to investigate whether this gene family may provide ICT response prediction. Methods: We assessed mRNA expression of DDR2 and its family member DDR1 . Transcriptome analysis of bladder cancer (BCa) models in which DDR1 and 2 were perturbed was used to derive DDR1 - and DDR2 -driven signature scores. DDR mRNA expression and gene signature scores were evaluated using BCa–The Cancer Genome Atlas (n = 259) and IMvigor210 (n = 298) datasets, and their relationship to BCa subtypes, pathway enrichment, and immune deconvolution analyses was performed. The potential of DDR - driven signatures to predict ICT response was evaluated and independently validated through a statistical framework in bladder and lung cancer cohorts. All statistical tests were 2-sided. Results: DDR1 and DDR2 showed mutually exclusive gene expression patterns in human tumors. DDR2 high BCa exhibited activation of immune pathways and a high immune score, indicative of a T-cell–inflamed phenotype, whereas DDR1 high BCa exhibited a non–T-cell–inflamed phenotype. In IMvigor210 cohort, tumors with high DDR1 (hazard ratio [HR] = 1.53, 95% confidence interval [CI] = 1.16 to 2.06; P = .003) or DDR2 (HR = 1.42, 95% CI = 1.01 to 1.92; P = .04) scores had poor overall survival. Of note, DDR2 high tumors from IMvigor210 and CheckMate 275 (n = 73) cohorts exhibited poorer overall survival (HR = 1.56, 95% CI = 1.20 to 2.06; P < .001) and progression-free survival (HR = 1.77 95%, CI = 1.05 to 3.00; P = .047), respectively. This result was validated in independent cancer datasets. Conclusions: These findings implicate DDR1 and DDR2 driven signature scores in predicting ICT response.